2020
DOI: 10.1159/000512206
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Cases of Autosomal Translocations in the Horse: Warmblood Family Segregating t(4;30) and a Cloned Arabian with a de novo t(12;25)

Abstract: We report 2 novel autosomal translocations in the horse. In Case 1, a breeding stallion with a balanced t(4p;30) had produced normal foals and those with congenital abnormalities. Of his 9 phenotypically normal offspring, 4 had normal karyotypes, 4 had balanced t(4p;30), and 1 carried an unbalanced translocation with tertiary trisomy of 4p. We argue that unbalanced forms of t(4p;30) are more tolerated and result in viable congenital abnormalities, without causing embryonic death like all other known equine aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Genomic DNA was isolated from EDTA-stabilized blood with QIAamp DNA Blood Mini Kit (Qiagen, Hilden, Germany). Both horses were tested by PCR for the Y-linked SRY gene and X-linked androgen receptor ( AR ) gene as described earlier [ 27 ], followed by genotyping for the 15 autosomal STRs of the standard equine parentage panel [ 28 ], and an additional 24 STRs specific for ECA26 ( Table 2 ). Genotyping was performed either with directly fluorescently labeled primers [ 29 ] or with three-primer nested PCR where the forward primer in each primer-pair had an M13-tail which was targeted by a fluorescently labeled universal M13 primer during PCR reactions [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated from EDTA-stabilized blood with QIAamp DNA Blood Mini Kit (Qiagen, Hilden, Germany). Both horses were tested by PCR for the Y-linked SRY gene and X-linked androgen receptor ( AR ) gene as described earlier [ 27 ], followed by genotyping for the 15 autosomal STRs of the standard equine parentage panel [ 28 ], and an additional 24 STRs specific for ECA26 ( Table 2 ). Genotyping was performed either with directly fluorescently labeled primers [ 29 ] or with three-primer nested PCR where the forward primer in each primer-pair had an M13-tail which was targeted by a fluorescently labeled universal M13 primer during PCR reactions [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Translocations can be broadly separated into two categories: balanced (the entire complement of genetic material is retained in all cells) and unbalanced (an unequal split between daughter cells, resulting in loss of genetic material in some cells). Of the 15 cases of equine translocations reported to date (Table 2), only a single male had an unbalanced autosomal translocation (64,XY,t(4;30),+4p) (Ghosh et al 2020), with the remaining being balanced autosomal or unbalanced allosomal translocations. Thirteen mares all presented with subfertility with six of 13 mares presenting with a specific history of recurrent pregnancy loss.…”
Section: Translocationsmentioning
confidence: 99%
“…[24][25][26] Other aberrations, such as XX/XY leukocyte chimerism and translocations, are diagnosed much less frequently in horses. [27][28][29][30][31][32][33][34][35] In most of those cases, horses were referred for research due to their reproductive problems. To date, the only screening study for equine karyotype abnormalities showed a prevalence of abnormalities in 2% of the entire study population and in 3.7% of the female population, 6 using classical cytogenetic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The second most common chromosomal disorder in horses is karyotype 64,XY Sry negative, identified in animals with a mare‐like phenotype, which belongs to a group collectively known as Disorders of Sex Development (DSD) 24–26 . Other aberrations, such as XX/XY leukocyte chimerism and translocations, are diagnosed much less frequently in horses 27–35 …”
Section: Introductionmentioning
confidence: 99%